Seeking SUMMERHILL: a self-study of my teacher education practices - Muchmore, James A.; Nogueira, Maria Ephigênia Cáceres (Revista Hipótese, 2018)
For the past 25 years, I have been slowly, inexorably movingtoward Summerhill. Inspired by the work of A. S. Neill and other progressive educators, my journey has involved a great deal of reflection about my role as a teacher, my relationship to students, and the nature of our work together. As a result, my approach to teaching has radically evolved from being a highly formal, tightly controlled, teacher-directed style—similar to what Freire has called the “banking model of education”—to one that is now much more open, inventive, and joyful. This self-study explores my evolution as a teacher educator, paying particular attention to some of the personal and pedagogical changes that I have experienced over the past two-and-a-half decades.
Keywords: Summerhill; Teaching; Self-study